A Phenomenography Perspective on Digital Transformation in Public Service: : Conceptions of Jogyakarta Smart Service (JSS) - Indrayani, Inri Inggrit; Priyowidodo, Gatut; Yogatama, Astri (The Journal of Society and Media, 2024)
The study aims to explore the actors' conceptions of the digitalization of public services through their experiences, perceptions, and understanding, which are not widely disclosed in research. These actors include the government as a service provider and users, as well as business actors and academicians. In principle, the sustainability of the digitalization of public services will be primarily determined by the participation and support of its users or citizens. The study used Phenomenography and interviewed eight informants, including three government officials, a citizen, an academic, and three business people, in Yogyakarta. The city introduced the JSS (Jogya Smart Service) one-door digital platform for public services in 2018. Data collection was conducted with interviews. The study revealed that actors had varying conceptions about the digitalization of public services. These differences were related to media use, advantages and challenges, and stakeholder engagement. Each perception had sub-perceptions, with public information digitalization having the most. The number of variations in the sub-conceptions indicates that each informant has a diverse perception and positive experiences related to implementing JSS. The outcome space demonstrated that digitalizing public services entails three understandings: new skills required, technological implications, co-production, and shared values.